LOCAL WISDOM AND ITS APPLICATION IN ARTS LEARNING AT SUNGAI RAYA STATE ELEMENTARY SCHOOL, KUBU RAYA REGENCY - Ghozali, Imam (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Local wisdom constitutes a mandatory content component within the arts and culture curriculum at every level of the educational system.This study aims to describe the implementation of local wisdom within the Merdeka Curriculum at elementary schools in Kubu Raya Regency. Local wisdom, as a source of cultural values, serves as a foundation for character formation and as a contextual learning resource. The Merdeka Curriculum, with its flexible framework, provides opportunities for schools to integrate local wisdom values into the learning process.This research employed a qualitative method with a descriptive-interpretative approach. Data were analyzed using an interactive analysis model involving data reduction, presentation, and conclusion drawing. The findings indicate that the potential for applying local wisdom in local elementary schools remains abundant. However, the limited competence of classroom teachers in understanding local wisdom has become a major obstacle in its implementation. The integration of local wisdom is influenced by teachers’ competence, school support, and community involvement. Among the three research subjects, one teacher implemented local wisdom in a planned manner, one did so unintentionally, and one did not apply it at all. It can be concluded that the application of local wisdom in cultural arts learning at the elementary level has not been fully optimized. Therefore, stronger educational policy support is required, particularly through teacher training and collaboration with local communities, to ensure that regional cultural values continue to be instilled as part of character education for students.